PENGARUH MODEL PEMBELAJARAN PROBLEM BASED LEARNING BERBANTUAN GOOGLE EARTH TERHADAP KEAKTIFAN BELAJAR IPAS SISWA KELAS V SDN 192 PEKANBARU - Dwi Nabila, Regi; Marhadi, Hendri; Guslinda (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study was motivated by the declining quality of learning, which is associated with the insufficient involvement of students in the learning process. The purpose of this study was to analyze the effect of implementing the Problem Based Learning (PBL) model assisted by Google Earth on the learning activeness of fifth grade students in Social and Natural Sciences (IPAS) at SD Negeri 192 Pekanbaru. This research employed a pre-experimental method using a one-group pretest-posttest design. The participants consisted of 25 fifth grade students. Data were collected through questionnaires, observations, and documentation. Quantitative data were analyzed using the one-sample t-test and effect size analysis. The results revealed that the implementation of the Google Earth-assisted Problem Based Learning model had a significant effect on students' learning activeness, with a significance value of 0.013 < 0.05. The effect size analysis yielded a coefficient of determination (r²) of 0.53, indicating that the learning model contributed 22.4% to students' learning activeness. Descriptive analysis showed an increase in the mean score of learning activeness from 49.84 in the pretest to 54.19 in the posttest. Students' learning activeness developed progressively across the aspects of receiving, responding, and valuing. Based on the findings, it can be concluded that the implementation of the Google Earth-assisted Problem Based Learning model significantly improved the learning activeness of IPAS students in fifth grade at SD Negeri 192 Pekanbaru.